Real-time model uncertainty in the United States: the Fed from 1996-2003 - Robert J. Tetlow; Brian Ironside (European Central Bank (ECB), 2006)
We study 30 vintages of FRB/US, the principal macro model used by the Federal Reserve Board staff for forecasting and policy analysis. To do this, we exploit archives of the model code, coefficients, baseline databases and stochastic shock sets stored after each FOMC meeting from the model's inception in July 1996 until November 2003. The period of study was one of important changes in the U.S. economy with a productivity boom, a stock market boom and bust, a recession, the Asia crisis, the Russian debt default, and an abrupt change in fiscal policy. We document the surprisingly large and consequential changes in model properties that occurred during this period and compute optimal Taylor-type rules for each vintage. We compare these optimal rules against plausible alternatives. Model uncertainty is shown to be a substantial problem; the efficacy of purportedly optimal policy rules should not be taken on faith.
Keywords: E37; E5; C5; C6; 330; monetary policy; real-time analysis; uncertainty; Wirtschaftsprognose; Prognoseverfahren; Makroökonometrie; Modellierung; Zentralbank; Schätzung; USA